Programmable supra-assembly of a DNA surface adapter for tunable chiral directional self-assembly of gold nanorods - Lan, Xiang; Liu, Na (Angewandte Chemie. International edition, 2017)
An important challenge in molecular assembly and hierarchical molecular engineering is to control and program the directional self-assembly into chiral structures. Here, we present a versatile DNA surface adapter that can programmably self-assemble into various chiral supramolecular architectures, thereby regulating the chiral directional “bonding” of gold nanorods decorated by the surface adapter. Distinct optical chirality relevant to the ensemble conformation is demonstrated from the assembled novel stair-like and coil-like gold nanorod chiral metastructures, which is strongly affected by the spatial arrangement of neighboring nanorod pair. Our strategy provides new avenues for fabrication of tunable optical metamaterials by manipulating the directional self-assembly of nanoparticles using programmable surface adapters.
Gesehen am 18.10.2018